Absorption Spectra of Ethyl Orange in Presence of Non-ionic Surfactant Solutions - Panchal, K.N.; Desai, A.S.; Nagar, T.N. (Asian Journal of Chemistry, 2016)
Spectrophotometric studies of ethyl orange–an azo dye in aqueous solutions containing various types of nonionic surfactants such as Triton x-114, Triton x-100, Triton x-102, Tween-20 and Tween-80–has been done below and above their critical micelle concentration. The absorption peak at 474 nm changes with the increases in concentration of the tritons above their critical micelle concentration and shift towards lower wavelength. The new peaks observed have been explained due to the formation of mixed micelles.